Development of Domestic Programming Technology - Lavrischeva, E. M. (Cybernetics and systems analysis, 2014)
This article considers the evolution of computer systems technologies on the way to the automation and creation of assembly lines. It presents fundamentals and objects of a technology of programming and assembling (composition of) complex systems from reusable resources (modules, objects, components, and services) that are configured in the form of variant structures of software systems assembled on production lines of software factories.